Potensi Senyawa Bioaktif Mangrove sebagai Bahan Aktif Fungsional dalam Formulasi Lip Balm: A Systematic Literature Review - Muhamad Afham; Eko Prasetyo Leu Amun Mama; Agustina Sartika Yos Ekaristi Manik; Dwi Cahya Rada (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
The increasing demand for natural and environmentally sustainable cosmetic products has stimulated interest in utilizing mangrove-derived bioactive compounds as alternative ingredients in lip balm formulations. Mangrove species are recognized as rich sources of secondary metabolites, including flavonoids, polyphenols, tannins, terpenoids, and natural lipids, which exhibit antioxidant and protective properties beneficial for lip care applications. This study aimed to systematically evaluate the potential of mangrove species as active ingredients in lip balm formulations by examining their phytochemical characteristics, antioxidant activities, and formulation performance. A Systematic Literature Review approach was employed following the PRISMA framework, involving the collection, screening, and synthesis of relevant studies published between 2020 and 2025. Eighteen eligible primary research articles were included in the final analysis. The results demonstrated that Sonneratia alba, Bruguiera gymnorrhiza, Ceriops tagal, Rhizophora mucronata, and Avicennia marina possess diverse bioactive compounds and promising antioxidant activities, with several species exhibiting very strong antioxidant capacity based on IC₅₀ values. Furthermore, lip balm formulations containing mangrove extracts generally fulfilled cosmetic quality requirements, including appropriate pH, good homogeneity, acceptable melting points, physical stability, and non-irritating properties. These findings highlight the potential of mangrove extracts as multifunctional natural ingredients for developing safe, effective, and sustainable lip balm products, while supporting the value-added utilization of coastal biological resources and promoting future innovation in natural cosmetic formulations.